2020
DOI: 10.1038/s41598-020-75880-2
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of smoking on age-related hearing loss in patients with diabetes

Abstract: This study investigated the synergistic effects of risk factors on age-related hearing loss (ARHL) using nationwide cross-sectional data of 33,552 individuals from the 2010‒2013 Korea National Health and Nutrition Examination Survey. Patients with ARHL were selected based on their pure-tone audiometry results. Previously reported risk factors for ARHL were analyzed using logistic regression and propensity score-matching, and synergistic effects between risk factors were analyzed using propensity score-matching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…We suggest a direct relationship between noise exposure and hearing loss. Previous evidence confirmed the role of noise exposure in the onset or progression of hearing impairment ( 27 , 46 ) through neuropathy of the end of the cochlea auditory nerve ( 47 ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We suggest a direct relationship between noise exposure and hearing loss. Previous evidence confirmed the role of noise exposure in the onset or progression of hearing impairment ( 27 , 46 ) through neuropathy of the end of the cochlea auditory nerve ( 47 ).…”
Section: Discussionmentioning
confidence: 81%
“…In our study, hearing loss was more common in men, even after adjustment for the effects of other variables. Most studies reported men had higher odds of hearing loss ( 18 21 , 26 , 27 ). It might reflect gender differences in exposure to other hearing loss risk factors such as lifestyle and CVD.…”
Section: Discussionmentioning
confidence: 99%
“…With an average participant age similar to ours, Tan et al 28 identified a graded association between Framingham Risk Score and hearing loss in the Busselton Healthy Ageing Study. Sun et al 23 found a higher number of metabolic syndrome components to be related to hearing loss in the NHANES and a separate NHANES study determined diabetes and smoking to be a particularly harmful combination 51 .…”
Section: Discussionmentioning
confidence: 99%
“…16 Few studies found out the significant relationship between hearing loss and smoking as revealed in this study. [17][18][19] A study done in Korea concluded that being a current smoker was significantly associated with hearing loss at all frequencies among workers exposed to occupational noise, and being a heavier smoker influenced lowfrequency hearing loss more greatly. 17 It has been well studied that the effect of nicotine causes vasoconstriction in the blood vessels.…”
Section: Discussionmentioning
confidence: 99%